A cross sectional study to assess the awareness and satisfaction level among the beneficiaries regarding Mission Indradhanush in selected districts of Indore division - Patidar, Anand Kumar; Khatri, Aaditya Kumar; Waskel, Bhagwan; Dixit, Sanjay (International Journal Of Community Medicine And Public Health, 2019)
Background: Only 62% (NFHS-4) of the infants in India are fully immunized which is much less than the desired goal of achieving 85% coverage. To accelerate the process of immunization by covering 5% and more children every year, the Mission Mode has been adopted to achieve target of full coverage by 2020. Mission Indradhanush will target all children under the age of two years and pregnant women with all available vaccines. Methods: It is a cross sectional study done in 3 randomly selected districts of Indore division. The beneficiaries selected were children <2 years and pregnant women. The selection of beneficiaries was done by exit interview technique. Data collection was done by using pre-designed, semi-structured questionnaire which assess the awareness and satisfaction level of the beneficiaries. Results: About 88% were aware about the immunization. Overall 78% beneficiaries agreed that vaccination is compulsory, 62% agreed that vaccination schedule should be followed, 30% beneficiaries considered that vaccination was harmful. Most of the beneficiaries were satisfied with behaviour of the health provider, with all key messages given by health provider. Conclusions: Most common reasons found for drop out or left out were, fear of side effects due to vaccination followed by lack of awareness regarding session sites. Satisfaction level was found relatively low regarding difficulty in finding the place where vaccination was done and distance of session sites.